Elan - California State College at Hayward::::::; California State University, Hayward::::::; California State University, East Bay:::::: (1967)
1967 Elan yearbook contains individual and group portraits of faculty, administrators, and students. Photographs of John Handy, Andres Segovia, Petula Clark, and Dr. Edward Teller who performed or spoke on campus during that academic year, are also included.